2002
DOI: 10.1177/00030651020500020701
|View full text |Cite
|
Sign up to set email alerts
|

The Priority of Primary Process Categorizing: Experimental Evidence Supporting a Psychoanalytic Developmental Hypothesis

Abstract: Earlier work has provided experimental evidence for the existence of the primary and secondary process mental organization posited by Freud and has demonstrated that primary process effects are the more active unconsciously (Brakel et al. 2000). Primary and secondary processes were assessed by a categorization test in which qualitatively different principles could be used. In new experiments using the same stimuli, another significant implication of Freud's model was tested: that primary process mental organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 15 publications
1
41
0
5
Order By: Relevance
“…The Wilcoxon Signed-Ranks (WSR) test (WSRZ=-3.043, p=.002), and Sign (S) test (SZ=-2.626, p=.009) show that ATTs predominate over RELs to a significant degree. The psychiatric patients are compared with a normal non-psychiatric population of a previous study called LifeCat in which the GeoCat was administered in exactly the same manner (Brakel et al, 2002), In this study, the distribution was already also non-normal but conformed to an inverse J-curve (KSZ=4.634; p<.001; see Figure 1 …”
Section: Attributional Responses In Psychiatric Versus Non-psychiatrimentioning
confidence: 99%
See 1 more Smart Citation
“…The Wilcoxon Signed-Ranks (WSR) test (WSRZ=-3.043, p=.002), and Sign (S) test (SZ=-2.626, p=.009) show that ATTs predominate over RELs to a significant degree. The psychiatric patients are compared with a normal non-psychiatric population of a previous study called LifeCat in which the GeoCat was administered in exactly the same manner (Brakel et al, 2002), In this study, the distribution was already also non-normal but conformed to an inverse J-curve (KSZ=4.634; p<.001; see Figure 1 …”
Section: Attributional Responses In Psychiatric Versus Non-psychiatrimentioning
confidence: 99%
“…Building on previous work (Brakel, 2009;Brakel, Shevrin, & Villa, 2002;Brakel, 2004;Brakel & Shevrin, 2005;Vanheule, Roelstraete, Geerardyn, Murphy, Bazan, & Brakel, 2011), this empirical study proposes to test if there is predominance of primary process mentation in psychosis as was proposed by Freud by applying a new method that has shown promise in mapping primary and secondary processes, called the GeoCat, an abbreviation of "Geometric Categorisaton" (Brakel, Kleinsorge, Snodgrass, & Shevrin, 2000; see further) in a population of psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, experimental studies employing non-verbal tasks to measure primary and secondary processes have shown that primary process thinking predominates in pre-schoolers and that at the age of seven years old, a shift occurs to secondary process thinking (Brakel & Shevrin, 2005;Brakel, Shevrin, & Villa, 2002).…”
Section: Body Boundaries and Primordial Mental Activitymentioning
confidence: 99%
“…Such a reexamination would necessarily have to address the evidence for primary process as exemplifying early childhood thinking and, consequently, as manifest in unconscious fantasies. Nevertheless, one still finds writers who retain much of Freud's original claim that the primary process, as described in adult dream construction, is characteristic of early childhood thinking (Brakel et al 2000;Brakel and Villa 2002;Brakel 2004).…”
Section: The Question Of Early Mentation: Moving Beyond Freud's Viewmentioning
confidence: 99%